What Influences State Civil Servants' Performance: An Analysis Of Work-Life Balance, Work Environment, And Compensation - M Fadhil (YUME : Journal of Management, 2022)
This study aims to identify and analyze simultaneously the effects of work-life balance, work environment, and compensation on the performance of the state civil apparatus in the Makassar City Regional Revenue Agency. We also measure which predictors have the greatest impact on performance. This study used primary data from a total population of 159 ASN with a sample method, namely a sample representing the total number of state civil apparatus in the Makassar City Regional Revenue Agency, which was 114 respondents, while the research period was carried out from July to December 2022. This study used descriptive data and statistical analysis. F-test results based on multiple regression were used to justify and verify hypotheses. This is indicated by the F-ratio and probability of 48.189 with a P-value of less than 0.05, in other words, accepting the hypothesis. Of the three variables selected, the index value shows that compensation (X3) is the strongest aspect with a value of 0.449, followed by work-life balance (X1) with a value of 0.318, and the work environment with a value of 0.315. These findings show how work-life balance, work environment, and compensation can improve the performance of the state civil apparatus in the Makassar City Regional Revenue Agency.Key words: work-life balance, work environment, compensation, performance